Not you: Frank O'Hara and the poetics of 'Personism'. Issue 3 (3rd March 2020) - Sullivan, Ryan D.
ABSTRACT: This article reads Frank O'Hara's 'Personism: a Manifesto' alongside his college journal and art writing, in order to argue for an understanding of 'Personism' as a poetics of persistent personhood that pushes against the lyric reading strategies of O'Hara's time. Writing in the 1950s and 60s, when homosexuality was not only subversive but illegal and dangerous, I argue that it is important to understand how particular reading strategies can potentially erase already marginalised voices. O'Hara's work defies dominant New Critical and phenomenological reading practices, which stripped poems of social particularity through intrusive lyric reading. Further, using Valerie Traub's notions of 'opaque knowledge' and 'relative autonomy', I explicate O'Hara's claim that 'art is not your life, it is somebody else's' in order to reconsider our reading practices and what effect they have on the ability of historical voices to assert themselves in the past.